Eu roaming regulation: Theoretical model suggests a positive assessment - Pio Baake; Lilo Wagner (DIW Weekly Report, 2018)
Since June 15, 2017, mobile network operators in the European Economic Area may not impose surcharges for making telephone calls, sending text messages, or using data services in other EEA countries. The regulation was designed to create a digital domestic market without adversely affecting consumers. The regulation raises the expectation of changes in mobile network operators' tariff structures. Theoretical examination shows that as long as mobile network operators do not exclude a roaming option for users who travel only occasionally, everyone will benefit from the regulations-even occasional travelers. In this case, positive effects are also anticipated for overall social welfare. However, negative effects are likely if some tariffs exclude a roaming option. The market result is highly dependent on how strongly consumers differ in their user behavior. The fact that all three mobile network operators in Germany exclusively offer tariffs with roaming options is evidence in favor of a positive assessment of the EU regulatory measures.
Keywords: L51; L96; D04; D86; 330; EU Roaming Regulation; Regulation Theory; Microeconomic Theory; Telecommunications Policy